2015
DOI: 10.3389/fpsyg.2015.00776
|View full text |Cite
|
Sign up to set email alerts
|

The default mode network as a biomarker for monitoring the therapeutic effects of meditation

Abstract: The default mode network (DMN) is a group of anatomically separate regions in the brain found to have synchronized patterns of activation in functional magnetic resonance imaging (fMRI). Mentation associated with the DMN includes processes such as mind wandering, autobiographical memory, self-reflective thought, envisioning the future, and considering the perspective of others. Abnormalities in the DMN have been linked to symptom severity in a variety of mental disorders indicating that the DMN could be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 142 publications
(190 reference statements)
3
61
1
Order By: Relevance
“…The parahippocampal gyrus is also an important part of the default mode network, which is thought to reflect mind wandering (Raichle, 2015), and has been previously shown to be deactivated with meditation (Simon and Engstrom, 2015). It is interesting to note, however, that the FC between the rACC/mPFC and the thalamus/parahippocampal gyrus was not specific to the MS, but was also observed during the RS, suggesting the learned deactivation through meditation extends into daily life.…”
Section: Discussionmentioning
confidence: 64%
“…The parahippocampal gyrus is also an important part of the default mode network, which is thought to reflect mind wandering (Raichle, 2015), and has been previously shown to be deactivated with meditation (Simon and Engstrom, 2015). It is interesting to note, however, that the FC between the rACC/mPFC and the thalamus/parahippocampal gyrus was not specific to the MS, but was also observed during the RS, suggesting the learned deactivation through meditation extends into daily life.…”
Section: Discussionmentioning
confidence: 64%
“…102 Default mode network activity and connectivity has been suggested as a potential biomarker for monitoring the therapeutic effects of meditation. 103 Specifically, whereas selfreferential processing and activity within the DMN is associated with mind wandering, the antithesis of mindful awareness of the present moment, mindfulness promotes de tach ment of identification with the contents of conscious thoughts, known as "reperceiving" or "decentering." 103,104 Activation of the DMN during mindful states is decreased in experienced meditators 105,106 and following MBSR training in meditation-naive participants, 107 and greater activation of the mPFC and functional connectivity of the mPFC with the DMN during rest (e.g., during self-referential processing) has been shown among meditators compared with controls 108 (Fig.…”
Section: The Triple Network Model Of Psychopathology and Ptsdmentioning
confidence: 99%
“…Results of our study point to the same direction: connectivity in regular meditators reflects less distraction or less interference during SWCT, outside the formal meditation practice. Simon and Engström (2015) have also suggested that DMN can be a biomarker to evaluate meditation effects on the treatment of mental disorders, such as anxiety or attention-deficit hyperactivity, because DMN abnormalities have been associated with the severity of their symptoms, and, on the other hand, meditation practice has been associated with DMN modulation.…”
Section: Discussionmentioning
confidence: 99%